2012
DOI: 10.1080/15562948.2012.646514
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Unique Experiences of Undocumented, Hispanic Women Who are Living in Poverty and Coping with Breast Cancer

Abstract: Understanding the experiences of recently immigrated women with breast cancer is essential to improving service delivery for this population. This qualitative study identified and explored the barriers to care, coping mechanisms, and overall healthcare experiences of a four recently immigrated Hispanic women diagnosed with breast cancer (three of whom were undocumented). The analysis revealed five major themes that were present across all four participants: psychological distress, barriers to access to care, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…He is going to know me". The views expressed above are similar to the findings of Gonzalez and Davis [26] who noted that the women they interviewed were also fearful and anxious about not being able to care for their children.…”
Section: Response To Diagnosissupporting
confidence: 82%
“…He is going to know me". The views expressed above are similar to the findings of Gonzalez and Davis [26] who noted that the women they interviewed were also fearful and anxious about not being able to care for their children.…”
Section: Response To Diagnosissupporting
confidence: 82%
“…As such, feelings and self-reports of existential and spiritual well-being protect against parental stress, which is often associated with lower income levels and lack of employment (Lamis, West, et al, 2014; Lamis, Wilson, Tarantino, Lansford, & Kaslow, 2014). Researchers have found that African American families, particularly women, utilize spirituality and religion as coping mechanisms to deal with life stressors, including, but not limited to poverty, health issues and chronic illness, grief, domestic violence, and bereavement (Chatters et al, 1999; Gonzalez & Davis, 2012; Musgrave, Allen, & Allen, 2002; Piraino, Krema, Williams, & Ferrari, 2014; Taylor & Chatters, 1988). Spirituality is considered to provide individuals with a sense of hope and strength and contributes to resiliency in the face of adversity by shaping appraisals of stress stimuli (McAdoo, 1995).…”
Section: Support From God and Spiritualitymentioning
confidence: 99%